2013
DOI: 10.1007/s00381-013-2236-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the basal ganglia in neurofibromatosis type 1

Abstract: These data confirm the presence of neuroaxonal damage with myelin disturbances in NF1 patients. We showed that metabolic and microstructural anomalies can be present in the same time in NF1 patients without developmental delay or cognitive deficits. Relations between brain anomalies, UBOs, and cognitive functions need further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Moreover, in the occipital cortex, GABA reductions were accompanied by lower glutamate and NAA + NAAG concentrations. This reduction in NAA is in agreement with earlier reports in subcortical structures 22 , 23 and WM. 24 The fact that both glutamate and NAA are altered might be explained by the tight link between these metabolites; they are interconnected through a series of biochemical reactions, mainly the tricarboxylic acid cycle and glutamate–glutamine cycle.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in the occipital cortex, GABA reductions were accompanied by lower glutamate and NAA + NAAG concentrations. This reduction in NAA is in agreement with earlier reports in subcortical structures 22 , 23 and WM. 24 The fact that both glutamate and NAA are altered might be explained by the tight link between these metabolites; they are interconnected through a series of biochemical reactions, mainly the tricarboxylic acid cycle and glutamate–glutamine cycle.…”
Section: Discussionsupporting
confidence: 93%
“…The NAA has been interpreted as a marker of neuronal viability and may be reduced in lesions or illnesses that deplete or replace the neuronal population (encephaloclastic processes or neoplasms). 25 Nicita et al, 26 in a multivoxel comparative analysis between NF1 patients with T2-W hyperintensities and controls, reported decreased NAA in the four regions of interest studied (although these values were the mean of left and right sides) as well as increased Cho and decrease Cr in three of the four ROIs, with a consequent decrease in the NAA/Cho ratio. 26 Barbier et al, 16 in another multivoxel study, compared metabolites in NF1 patients with and without T2-W hyperintensities and observed a decrease in NAA/Cr, NAA/ Mi, and NAA/Cho ratios, and an increase in Mi/Cho ratio statistically significant just for the lateral region of the thalamus.…”
Section: Figurementioning
confidence: 96%
“…These results could suggest a thalamic dysfunction that affects the thalamo-cortico-frontal loops related to neural and/or astroglial abnormalities. In a multimodal approach that combines spectroscopy MRI and DTI, Nicita et al (39) analyzed spectroscopy imaging and 2 DTI parameters (ADC and FA) for 4 regions of interest (the caudate nucleus, the globus pallidus, the putamen and the thalamus) in 14 NF1 subjects aged 8 to 31 years and 8 healthy controls. The authors found (1) lower NAA, NAA/choline and NAA/creatinine ratios regardless of the subject's age (under or above 18 years of age) and the presence or absence of UBOs when the NF1 subjects were compared with the controls; (2) and a higher ADC without FA changes in UBOs subjects and subjects under 18 years of age.…”
Section: Multimodal Approachmentioning
confidence: 99%